2008
DOI: 10.1002/pts.839
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan tailor‐made films: the effects of additives on barrier and mechanical properties

Abstract: With the aim of achieving 'tailor-made' chitosan fi lms, the effects of several variables on the properties of chitosan fi lms were studied. These variables were chitosan concentration and molecular weight of thermally depolymerized chitosan, addition of lipids (palmitic acid, beeswax or carnauba wax) and plasticizer (glycerol). The water vapour transmission rate (WVTR) and mechanical properties of these fi lms were measured. The innovative feature of this study is that it provides specifi c information to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 26 publications
4
50
0
16
Order By: Relevance
“…anionic groups) and consequently, reducing their availability to a level that will not sustain growth of the pathogen form the films (Bautista-Baños et al 2006). The present results suggested that this barrier to water soluble nutrients could be most effective for chitosans of lower molar mass and low F A , since it was observed that the water permeability of chitosan films was 50% reduced when molar mass of the original chitosan was reduced from 235 kDa (DP 1,383) to approximately 13.7 kDa (DP 45), which was also reported by Yoshida et al (2008). Chitosan coating observed on the surface of the mycelia suggested that the fungal growth inhibition could be explained by a direct interaction of chitosan on the fungal cell wall as a consequence of polycationic nature of chitosan.…”
Section: Resultssupporting
confidence: 86%
“…anionic groups) and consequently, reducing their availability to a level that will not sustain growth of the pathogen form the films (Bautista-Baños et al 2006). The present results suggested that this barrier to water soluble nutrients could be most effective for chitosans of lower molar mass and low F A , since it was observed that the water permeability of chitosan films was 50% reduced when molar mass of the original chitosan was reduced from 235 kDa (DP 1,383) to approximately 13.7 kDa (DP 45), which was also reported by Yoshida et al (2008). Chitosan coating observed on the surface of the mycelia suggested that the fungal growth inhibition could be explained by a direct interaction of chitosan on the fungal cell wall as a consequence of polycationic nature of chitosan.…”
Section: Resultssupporting
confidence: 86%
“…Para o preparo dos filmes das amostras de quitosana seguiu-se o procedimento descrito por Yoshida et al [16] . Os filmes foram preparados dissolvendo as amostras de quitosana em solução de ácido acético 1% nas concentrações 0,25, 0,5, 1,0 e 1,5%.…”
Section: Produção Dos Filmes De Quitosanaunclassified
“…A metodologia de produção foi adaptada de [15] . Os filmes foram produzidos por via úmida, solubilizando 2,00 g/100 g de suspensão filmogênica de quitosana, contendo o indicador colorimétrico clorofila na concentração de 0,25 g/100 g. Ácido acético foi adicionado estequiometricamente, de acordo com o grau de acetilação e massa de quitosana, para promover a protonação dos grupos NH 2 [32] .…”
Section: Filmes Inteligentes De Quitosana (Fiq)unclassified
“…Nesta última década, inúmeros estudos foram desenvolvidos visando a produção e caracterização de filmes biodegradáveis à base de macromoléculas naturais, como proteínas de soro de leite [6,7] , gelatina [8][9][10] , zeína [11][12][13] , quitosana [14][15][16][17] , quinoa [18] , amido de mandioca [19][20][21][22] , proteína de soja [23] , pectina [24] , alginato [25][26] , entre outros. Entretanto, a abordagem de aplicação destes materiais como sensores em embalagens inteligentes, ainda é escassa na literatura especializada.…”
Section: Introductionunclassified